How to solve 3x2+2√6x+2?

solve by factorization,by completing the square or by quadratic formula but more preferably by factorization

Discriminant = √[(2√6)^2 - 4 * 3 * 2] = 0

=> 3x^2 + 2√6x + 2 is a perfect square and is

= (√3x + √2)^2

An expression cannot be solved. It can be simplified. If you are meaning to solve the equation

3x^2 + 2√6x + 2 =, then its is

(√3x + √2)^2 = 0

=> x = - √(2/3).

Oct 16 at 6:22

[root3x}^2+ 2 X root3x X root2 + [root 2]^2

[Root3x + root 2] ^2

Oct 16 at 10:8

I hope you know your lack of brackets has made this thing unreadable. Does the square root only cover the 6? Does it go all the way to the 2?

Oct 16 at 14:17

In given form , question has no mathematical meaning.

Could there be an = sign somewhere?

Could there be a zero somewhere?

Oct 16 at 18:49

3x2+2√6x+2 =

(x√3 + √2)2

then x = -√2/√3 double root

Oct 16 at 23:44

you put brackets to break down the sum

3x2+2√6x+2

(3x2+2)(√6x+2)

3+2=5+x2=5x2

5x2√8x

because you don't know what x2 is you just have to leave it at that unless in gives you the number for what x2 stands for

i don't know if this is right i am just guessing lol

Oct 17 at 5:2

well .. by looking at it , it tells ..

3x2 = (√3x)2 = a2

2 = (√2)2 = b2

and 2√6 = 2.√3.√2 = 2ab

=> 3x2+2√6x+2 = (√3x + √2)2

==> x= -√(2/3)

NOTE : i did these kinds of sums so i could figure out that it was a whole square by looking at the nos.

bt .. i would suggest you to find out the discriminant (b2-4ac) before solving .. which comes out to be 0 .. indicating it has equal roots .. which means it is a perfect square ! :)

Oct 17 at 10:44